Key Trends That Will Shape Army Installations of Tomorrow - Lachman, Beth E. (RAND Corporation, 2013)
Army installations of the future will most likely be shaped and influenced by trends and pressures external to the Army, such as technology changes and land-use pressures. RAND Arroyo Center conducted a study for the Army's Office of the Assistant Chief of Staff for Installation Management to assess how future trends external to Army installations may affect the Army's ability to provide quality installation services and infrastructure.